Women’s empowerment, productivity, and food security: Nationally representative panel data analysis in Malawi - Ragasa, Catherine; Carrillo, Lucia; Ma, Ning (International Food Policy Research Institute, 2023)
This paper provides new evidence on the relationship between intrahousehold dynamics, agricultural productivity, and dietary diversity using a nationally representative panel household dataset in Malawi (two waves: 2019 and 2021, with 5,067 female and male respondents per wave). We used the Abbreviated Women’s Empowerment in Agriculture Index (A-WEAI) indicators, complemented by intrahousehold dynamics in access to extension services and technology awareness and adoption. Panel data were analyzed using household fixed effect models. Results show that the majority of farms were jointly managed by women and men; jointness in plot management has been increasing over time, highlighting the critical need to look at jointness in decision-making. Of rural women sampled, 20% did not achieve empowerment, and the main contributors to their disempowerment were lack of group membership and lack of access and control over financial resources. Results also show that women’s education and their access to extension are significantly associated with their empowerment. Women’s empowerment indicators significantly explain much of the variations in crop productivity and dietary diversity. The impact of women’s empowerment on crop productivity was similar across asset quintiles, but the impact on dietary diversity was larger within the poorest household quintile.